Towards a Secure Medium Access Control Protocol for Cluster-Based Underwater Wireless Sensor Networks. (14th May 2015) - Xu, Ming; Liu, Guangzhong; Guan, Jihong
The unique characteristics of high bit error rate, low bandwidth, and long propagation delay in underwater environments pose significant challenges to the design of the medium access control (MAC) protocol for underwater wireless sensor networks (UWSNs). Clustering is an effective and practical way to enhance the performance of UWSNs. In this paper, we propose a secure MAC protocol for cluster-based UWSNs, called SC-MAC, which aims to ensure the security of data transmission. In SC-MAC, the clusters are formed and updated dynamically and securely. We leverage MAC layer information by considering the link quality as well as residual energy of the modem's battery. After the successful mutual authentication, all sensor nodes from different clusters can protect the data transmission in the continuous communication. As the states of sensor nodes may not be observed accurately in a harsh underwater environment, we formulate the channel scheduling process as a stochastic partially observed Markov decision process (POMDP) multiarmed bandit problem and derive the optimal channel scheduling rules hereby. Simulation results show that SC-MAC can perform better than existing state-of-the-art MAC protocols in terms of network throughput, successful delivery ratio, and energy consumption in various circumstances.